Dipole–dipole interactions enhance non-Markovianity and protect information against dissipation*Project supported by the National Key Research and Development Program of China (Grant Nos. 2017YFA0304100 and 2016YFA0302700), the National Natural Science Foundation of China (Grant Nos. 61327901, 11474267, 11774335, and 61322506), the Key Research Program of Frontier Sciences, Chinese Academy of Sciences (Grant No. QYZDY-SSW-SLH003), the Fundamental Research Funds for the Central Universities, China (Grnat No. WK2470000026), the National Postdoctoral Program for Innovative Talents, China (Grant No. BX201600146), China Postdoctoral Science Foundation (Grant No. 2017M612073), and Anhui Initiative in Quantum Information Technologies, China (Grant No. AHY020100). The author Munsif Jan is thankful to the China Scholarship Council (CSC) for financial support (Grant No. 10358). (September 2019) - Jan, Munsif; Xu 许, Xiao-Ye 小冶; Wang 王, Qin-Qin 琴琴; Chen 陈, Zhe 哲; Han 韩, Yong-Jian 永建; Li 李, Chuan-Feng 传锋; Guo 郭, Guang-Can 光灿
Abstract : Preserving non-Markovianity and quantum entanglement from decoherence effect is of theoretical and practical significance in the quantum information processing technologies. In this context, we study a system S that is initially correlated with an ancilla A, which interacts with the environment E via an amplitude damping channel. We also consider dipole-dipole interactions (DDIs) between the system and ancilla, which are responsible for strong correlations. We investigate the impact of DDIs and detuning on the non-Markovianity and information exchange in different environments. We show that DDIs are not only better than detuning at protecting the information (without destroying the memory effect) but also induce memory by causing a transition from Markovian to non-Markovian dynamics. In contrast, although detuning also protects the information, it causes a transition from non-Markovian to the Markovian dynamics. In addition, we demonstrate that the non-Markovianity grows with increasing DDI strength and diminishes with increasing detuning. We also show that the effects of negative detuning and DDIs can cancel out each other, causing a certain loss of coherence and information.